SYSTEMATIC LITERATURE REVIEW OF THE ROLE OF ONTOLOGY, EPISTEMOLOGY AND AXIOLOGY IN MANAGEMENT RESEARCH IN THE DIGITALIZATION ERA- MSMES IN VARIOUS COUNTRIES - Sarida Sirait; Formaida Tambunan; Mutia Nurhalizah; Mujiatun Mujiatun (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This article presents a systematic literature review (SLR) on Ontology, Epistomology, Management Axiology, Digital, Financial, fostering innovation, and supporting economic performance and sustainability. Based on a collection of articles from reputable international journals (2023–2025), this review identifies three main clusters: (1) digital finance and financial deepening and growth; (2) digital financial innovation, inclusion, and financial resilience; and (3) digital finance, technological innovation, and sustainability performance (green innovation and carbon emissions). The synthesis shows that digital financial innovation consistently contributes positively to financial deepening, corporate innovation, financing efficiency, and economic growth, but its effects depend on the institutional context, digital financial literacy, and regulatory design. The article concludes with a research agenda that emphasizes the need to integrate green-sustainable finance perspectives, developing country contexts, and more diverse methodological approaches. Keywords: Ontology, Epistomology, Management Axiology, Digital, Financial. Abstrak: Artikel ini menyajikan tinjauan literatur sistematis (SLR) tentang Ontologi, Epistemologi, Aksiologi Manajemen, Digital, Keuangan, mendorong inovasi, dan mendukung kinerja ekonomi dan keberlanjutan. Berdasarkan kumpulan artikel dari jurnal internasional terkemuka (2023–2025), tinjauan ini mengidentifikasi tiga klaster utama: (1) keuangan digital dan pendalaman serta pertumbuhan keuangan; (2) inovasi keuangan digital, inklusi, dan ketahanan keuangan; dan (3) keuangan digital, inovasi teknologi, dan kinerja keberlanjutan (inovasi hijau dan emisi karbon). Sintesis menunjukkan bahwa inovasi keuangan digital secara konsisten memberikan kontribusi positif terhadap pendalaman keuangan, inovasi perusahaan, efisiensi pembiayaan, dan pertumbuhan ekonomi, tetapi dampaknya bergantung pada konteks kelembagaan, literasi keuangan digital, dan desain regulasi. Artikel ini diakhiri dengan agenda penelitian yang menekankan perlunya mengintegrasikan perspektif keuangan hijau-berkelanjutan, konteks negara berkembang, dan pendekatan metodologis yang lebih beragam.. Kata kunci: Ontologi, Epistemologi, Aksiologi Manajemen, Digital, Keuangan